A tensegrity approach to the optimal reinforcement of masonry domes and vaults through fiber-reinforced composite materials. (15th December 2015) - Fraternali, F.; Carpentieri, G.; Modano, M.; Fabbrocino, F.; Skelton, R.E.
Abstract: We present a tensegrity approach to the strengthening of masonry vaults and domes performed by bonding grids of fiber reinforced composites to the masonry substrate. A topology optimization of such a reinforcement technique is formulated, on accounting for a tensegrity model of the reinforced structure; a minimal mass design strategy; different yield strengths of the masonry struts and tensile composite reinforcements; and multiple loading conditions. We show that the given optimization strategy can be profitably employed to rationally design fiber-reinforced composite material reinforcements of existing or new masonry vaults and domes, making use of the safe theorem of limit analysis. A wide collection of numerical examples dealing with real-life masonry domes and vaults highlight the technical potential of the proposed approach.